Análise de decisão multicritério para avaliação de alternativas de recolhimento de palhiço de cana-de-açúcar para a cogeração de energia - Lemos, Paula Horta (Universidade Federal de São Carlos, 2018)
The sugar and alcohol industry is among the most traditional and old biomass processing industries in Brazil. Cane biomass is divided into two categories: sugarcane bagasse, available in the industry after the extraction of the juice and already used as an energy input; and the trash, object of study of this research, that is available in the field after the cane harvest. With the permanence of trash in the soil after the prohibition of pre-burning in manual harvesting, new problems have arisen, such as pest infestation and cane sprout retardation. An alternative to excess trash in the field, can be the collection of this biomass in the field for cogeneration of energy. However, the high cost associated with the collection of trash is the most plausible explanation for the small generation of surplus energy by the sector. The most widely used picking alternatives are the whole harvest, partial harvest and the baling. In the alternative of integral harvest, the cane and the trash are transported to the plant, where in a cleaning station the separation of the trash is carried out. On the other hand, in the partial harvest part of the trash is in the soil and the other part of the trash is transported along with the cane for industry and then they are separated in the cleaning station. In the baling, after the conventional mechanized harvest, the trash is left in the field for natural drying, after which the trash is enclose, packaged in the field and transported to the plant. Many criteria should be taken into account when choosing the best alternative in the process of obtaining trash, such as transportation costs, trash wetness, trash quality, separation efficiency of the cane and trash, investment and operating costs with collection, revenue from cogeneration, among others, thus there is a trade off in relation to these criteria and the alternatives for collecting trash. Thus, a generic multicriteria decision analysis model was elaborated from the SMART tool (Simple Multi-Attribute Ranking Technique) to assist companies in the sugar and alcohol industry on the alternative of collecting trash for the cogeneration of energy. The model was applied in mills of the sector. As a provisional result, the integral harvest and baling option were the suggested alternatives. However, the proposed approach allowed us to robustly analyze the most appropriate decision by means of sensitivity analyzes such as variation in the weights os the cited criteria and Monte Carlo analysis for energy price variation. After a Monte Carlo analysis, the results showed that at 41% of the simulated energy prices the recommended solution is a harvest integral. The solution suggested by the methodology is not the optimal solution in visible cost. On the other hand, it provides the best overall performance by meeting the criteria of the hierarchical structure of objectives. In addition to an acceptable cost and a high expected value of revenue, this solution satisfies other needs of the model, this is an important contribution, especially in cases where many conflicting objectives appear.
Keywords: Cana-de-açúcar; Recolhimento de palhiço; Cogeração de energia; Análise de decisão multicritério; Sugarcane; Trash collection; Energy cogeneration; Multicriteria decision analysis; Biomassa; Biomass; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO